(untitled) (Ta’limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2024)
Annotation. Over the centuries, many inventions have been made by scientists and they continue to benefit mankind to this day. For instance, a wheel, paper, a light bulb, a television, a vacuum cleaner and so on. Inventions continue nowadays, new kinds of things are created day by day. And we are reading about them in our warm place over a cup of tea and share such news with our loved ones. So where did the Internet that shares all the information come from and who created it?